Large-scale analysis reveals the specific clinical and immune features of B7-H3 in glioma. (2nd November 2018) - Zhang, Chaoqi; Zhang, Zhen; Li, Feng; Shen, Zhibo; Qiao, Yamin; Li, Lifeng; Liu, Shasha; Song, Mengjia; Zhao, Xuan; Ren, Feifei; He, Qianyi; Yang, Bo; et al.
ABSTRACT: Background: B7-H3 is an immune checkpoint member that belongs to B7-CD28 families and plays a vital role in the inhibition of T-cell function. Importantly, B7-H3 is widely overexpressed on solid tumors, making it become an attractive target for cancer immunotherapy. To clarify the expression panel of B7-H3 in glioma, we explored the clinical and immune features of B7-H3 expression in a large-scale study. Methods and patients : Totally, 1323 glioma samples from Chinese Glioma Genome Atlas (CGGA) dataset, including 325 RNAseq data and 301 mRNA microarray data, and The Cancer Genome Atlas (TCGA) dataset, including 697 RNAseq data, were gathered into our research. The statistical analysis and graphical work were mainly realized by R language. Results: B7-H3 expression was found positively correlated with the grade of malignancy, which might be caused by hypomethylation. The expression level of B7-H3 was consistently up-regulated in IDH wild-type glioma and highly enriched in mesenchymal subtype. GSEA analysis suggested that B7-H3 related genes were more involved in immune response and angiogenesis in glioma. Moreover, B7-H3 showed a consistent positive relationship with stromal and immune cell populations. Further analysis confirmed that B7-H3 played an important role in T-cell-mediated immunity, especially in T-cell-mediated immune response to tumor cell. Circos plots revealed that B7-H3 was tightly associated with most B7 members and other immune checkpoints. Univariate and multivariate cox analysis demonstrated that B7-H3 was an independent prognosticator for glioma patients. Conclusion: B7-H3 represents the malignant phenotype of glioma and independently predicted worse prognosis in glioma patients. Moreover, B7-H3 collaborating with other checkpoint members may contribute to the dysfunctional phenotype of T cell. These findings will be helpful for further optimizing immunotherapies for glioma.